Digital Customer Experience: Retrospective Insights And Future Directions - Yeane Koyongian; Deske W. Mandagi (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
The rapid acceleration of digital transformation and rising customer expectations have positioned Digital Customer Experience (DCX) as a critical yet fragmented research domain. This study systematically reviews the DCX literature to identify key research trends, dominant themes, theoretical foundations, and methodological approaches. Using a PRISMA-guided systematic literature review of 365 Scopus-indexed journal articles, the study employs bibliometric and content analysis techniques. The findings reveal a significant increase in DCX research, particularly after 2020, with core themes centered on customer experience, digital transformation, and digital marketing. Six major thematic clusters emerge, including value creation, technology, engagement, consumer behavior, customer journey, and business performance. The results also indicate a dominance of qualitative and conceptual studies, alongside a growing adoption of quantitative methods such as structural equation modeling. Despite diverse theoretical applications, the field remains fragmented, highlighting the need for integrative frameworks. This study contributes by consolidating the intellectual structure of DCX research and proposing future research directions using the TCCM framework. Practically, it offers insights for organizations to design integrated and customer-centric digital experiences that enhance engagement, satisfaction, and competitive advantage